Main Cardiovascular Risk Factors in Bank Employee of Guilan in 2016 - Zahra Mohtasham-Amiri; Mohammad Asadian-Rad; Mohammad Khademloo; Zahra AbbasiRanjbar; Abbas Jafari-Shakib; Maryam Kiaei; Laila Kouchakinezhad-Eramsadati (Shahid Beheshti University of Medical Sciences, 2018)
Background and Objectives: Cardiovascular diseases are the fist cause of death in the world، and Iran. It seems that some jobs such as bank employees due to sedentary lifestyle are at a higher risk of cardiovascular diseases than the general population. Therefore this study was done to determine the risk factors in Bank Employee-North of Iran in 2016. Material and Methods: This cross sectional study was conducted among 488 bank employees were selected from total staff lists by simple random sampling. Demographic data، the underlying disease، physical activity and smoking were collected by interviewing them. In addition،blood lipid profie, fasting blood sugar, serum level of vitamin D, blood pressure, height and weight were measured for each participants. Results: The mean (SD) age of participants was 43.3(6.1) years and the minimum and maximum age was (30 and 59) underwent this study. 445(91.2%) was male. 36(12.9%) were smoking. High blood pressure and Diabetes were prevalent as 78(15.9%) and 31(6.3%) respectively. Dyslipidemia were observed in over 30% and 373(76.5%) of all participants had obesity and overweight. In terms of major risk factors، including hypertension, high cholesterol, diabetes and obesity, only 15(3%) had no risk factor and the rest suffered at least one of these risk factors. Conclusion: The study showed that the family directly and indirectly affects becoming a victim of bullying. Parent-child relation forms adolescent behavior patterns. Therefore, training parents in appropriate child raising methods could play an important role in preventing much social harm in the future.